Will an Implementation of “Joy of Life in Nursing Homes” Have Positive Effect for the Work Culture? A Comparison Between Two Norwegian Municipalities - André, Beate; Heldal, Frode; Sjøvold, Endre; Haugan, Gørill (Frontiers in Psychology, 2021)
Background Currently, we are facing a demographic shift to an older population and its consequences worldwide: in the years to come, several older people will need nursing home (NH) care. The work culture is important for care quality in NHs. Some Norwegian municipalities have implemented the Joy of Life Nursing Home (JoLNH) strategy, representing a resource-oriented health-promoting approach. Knowledge about how implementation of the JoLNH approach impacts the work culture is scarce. Aimss We hypothesized that the JoLNH strategy impacts positively on the work culture: (1) when comparing measurements at two time points (T1 and T2) and (2) when comparing two municipalities, among which one has implemented the JoLNH and the other has not. Method With a 1-year interval, healthcare personnel in 43 NHs located in two large Norwegian municipalities responded to a survey in two waves (T1 and T2). In total, 558 healthcare personnel participated at T1 and 515 at T2. Work culture was assessed by the Systematizing Person–Group Relations Instrument (SPGR). Findings The municipality implementing the JOLNH strategy experienced significant increases in SPGR dimensions, representing positive orientations towards a better work culture, whereas those working in the non-JoLNH municipality reported an increase in SPGR dimensions, signifying a worsened work culture. Discussion The data indicate that the implemented JoLNH strategy has endorsed positive effects in the work culture. The JoLNH strategy emphasizes on the quality of patient care, which is what healthcare personnel, in general, are much concerned about. Furthermore, attention to task orientation and independent work seem to encourage a better work culture in NHs. Conclusion This study suggests that the JoLNH strategy impacts positively on the work culture in Norwegian NHs.